The Effect of Country-of-Origin Brand Image and Brand Product on Attitude in Choosing Smartphone Products (Jurnal Manajemen Bisnis, 2022)
The purpose of this study is to analyze and investigate the relationship between country of origin and brand variables on consumer attitudes. The sample selection used a student sample from ITB Nobel Indonesia students, totaling 343 samples. The results of the study state that the country of origin has a positive and significant effect on consumer attitudes, as well as brands which also have a positive and significant effect on consumer attitudes.